Study of Variations in the Origin and Course of Musculocutaneous Nerve - Sonje, Dr P. D.; Gupta, Dr P.; Vatsalaswamy, Dr P (International Journal of Innovative Research in Medical Science, 2016)
Variations in the origin ,course,branching pattern, termination and connection of the musculocutaneous nerve are not uncommon.The musculocutaneous nerve arises from the lateral cord of brachial plexus,opposite the lower border of pectoralis minor , pierces the coracobrachialis, descends laterally between the biceps and brachialis to the lateral side of arm and just below the elbow it pierces deep fascia lateral to the tendon of biceps brachii to continue as lateral cutaneous nerve of forearm.The aim was to study the variations in the origin and course of musculocutaneous nerve.Variations like musculocutaneous nerve did not pierce the coracobrachialis muscle, musculocutaneous nerve forming communications with median nerve were found in the present study. Knowledge of these variations is important for surgeons, clinicians and anatomists.Awareness of possible variations is essential to avoid unexpected complications during surgical procedures such as brachial plexus block, arthroscopy of shoulder joint and repair of fractures of humerus.